North Atlantic influence on Holocene flooding in the southern Greater Caucasus. (April 2018) - von Suchodoletz, Hans; Zielhofer, Christoph; Hoth, Silvan; Umlauft, Josefine; Schneider, Birgit; Zeeden, Christian; Sukhishvili, Lasha; Faust, Dominik
In the context of global climate change, flooding becomes an increasingly serious threat to modern societies, and future flooding can only be understood using long-term geological flood records also encompassing Holocene climate variability. Unlike other regions, Holocene flooding in the Caucasus region is only poorly understood so far: Whereas some rivers originating from the Lesser Caucasus were investigated, no studies exist about rivers originating from the Greater Caucasus. This study investigated the Holocene fluvial dynamics of the upper Alazani River in the southern Greater Caucasus using chronostratigraphic and sedimentologic methods applied to a fluvial sediment-paleosol sequence. By comparing these data with other paleoenvironmental and regional recent hydroclimatic data, we aimed to identify the main drivers of Holocene flooding in the southern Greater Caucasus. Our study shows a link between fluvial sedimentation around 7.3, 5.4, 3.8–2.9 and around 1.7 cal. ka BP and North Atlantic Bond events. Although probably caused by a discharge maximum during spring, fluvial sedimentation is coeval with low regional spring precipitation. As supported by recent hydroclimatic data, intensified floods during Bond events could possibly be explained with more intensive precipitation but also a prolonged snow season during colder winters. The latter would lead to more spring meltwater and thus more intensive spring discharge. Consequently, given increasing annual temperatures because of human-caused global warming, the flood maxima of pluvio-nival rivers in the southern Greater Caucasus may be expected to decrease during the next decades. Our findings underline the need of geological flood records to understand future flood patterns of rivers in mountain regions with complex runoff regimes.